Snow falling on cedars [videorecording (DVD)] - Howard, James Newton (2000)
A murder trial has upset the quiet community of San Piedro, and now this tranquil village has become the center of controversy. For a local reporter the trial strikes home when he finds his ex-lover is linked to the case.